2019
DOI: 10.1080/09515089.2019.1697803
|View full text |Cite|
|
Sign up to set email alerts
|

Research on group differences in intelligence: A defense of free inquiry

Abstract: In a very short time, it is likely that we will identify many of the genetic variants underlying individual differences in intelligence. We should be prepared for the possibility that these variants are not distributed identically among all geographic populations, and that this explains some of the phenotypic differences in measured intelligence among groups. However, some philosophers and scientists believe that we should refrain from conducting research that might demonstrate the (partly) genetic origin of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…We then spell out why the existence of group differences may not be as worrisome as some people fear. In fact, we think, hostility toward people who conduct research into group differences, or toward people who summarize that research publicly, may be producing more harm than the research itself (Anomaly 2017;Carl 2018;Cofnas 2020). 2…”
Section: The Taboo Of Group Differencesmentioning
confidence: 99%
“…We then spell out why the existence of group differences may not be as worrisome as some people fear. In fact, we think, hostility toward people who conduct research into group differences, or toward people who summarize that research publicly, may be producing more harm than the research itself (Anomaly 2017;Carl 2018;Cofnas 2020). 2…”
Section: The Taboo Of Group Differencesmentioning
confidence: 99%
“…Cognitive ability is a valuable human attribute in so far as it has been shown that it has implications for life outcomes (Serpell, 1993;Lo, 2017;Cofnas, 2020). Opoku (2012, p. 538) has defined cognitive abilities as "all activities generated from within the conscious mind which influence our behavior."…”
Section: Introductionmentioning
confidence: 99%
“…The definition, measurement, and research around intelligence is both popular and controversial (Lo, 2017;Oppong, 2017a;Cofnas, 2020). A more controversial aspect of intelligence research has been the persistent attempts (speculatively or empirically) to explain the group differences in terms of genotypic variance (Deary et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…intelligence are due to environmental factors (Cofnas, 2019). According to a researcher in his paper that the mean intelligence quotients of 11-year old children living in rural areas have been compared with those of children in urban areas.…”
mentioning
confidence: 99%